Comparative Study of Steel, Bamboo and Glass Fiber as reinforcing material in Concrete Beams : A Review - Kumar, Anand; Supe, Jayant (International Journal of Scientific Research in Civil Engineering, 2020)
Concrete is the most principally utilized material in the development field took after by steel as reinforcements. The present day situation is seeing a quick change in the building material industry and step by step new innovations are supplanting the ordinarily utilized materials. Scientists everywhere throughout the world are endeavoring to enhance concrete by the utilization of fibers, pozzolanas and different admixtures. Steel is given in the pressure side fundamentally in order to balance the powerless zone of concrete that is Tension. In spite of the fact that it is thought to be the best for this work yet at the same time it gets eroded by the activity of the nature in this way, emerges the point of searching for an option. A standout amongst the most well-known choices is Fiber strengthened polymer rebars (FRP’s). In the present trial examination supplanting of Ordinary Concrete with Glass fiber and bamboo fiber Reinforced Concrete along these lines considered on the progressions of Compressive Strength and Ultimate Crushing loads In This study e are reviewing publications related to advancement in concrete technology and development.